Faktor-Faktor yang Berhubungan dengan Underweight pada Anak Usia 6-23 Bulan di Pagedangan Kabupaten Tangerang - Aprilya Roza Werdani; Justiyulfah Syah (Nutrition Science and Health Research, 2023)
Underweight is a crucial indicator of malnutrition in children and has long-term effects such as physical health problems, behavioral problems, and low educational achievement. Objective. This study aimed to assess associated factors of underweight among children aged 6-23 months in Pagedangan, Tangerang District. Method. This study uses a cross-sectional design used to conduct this study. Anthropometric measurements and questionnaire interviews were carried out for data collection. Data were analyzed using univariate and chi-square tests. Result. This study showed that the proportion of underweight was 18.0%. Of 150 children aged 6-23 months, 8% were born with low birth weight, 44.0% had a history of acute respiratory infection, 32.0% had a deficit of energy, 32.7% had a deficit of fat, 39.3% had a deficit of carbohydrate, and 53.3% had a deficit of protein. Energy intake (OR 3.021, 95% CI 1.288-7.087), carbohydrate intake (OR 3,279, 95% CI 1.380-7,790), and history of acute respiratory infection (OR 3.125, 95% CI 1.298-7.522) were significantly associated with underweight. Conclusion. The proportion of underweight children aged 6-23 months in the Pagedangan sub-district is higher than the national prevalence. Energy intake, carbohydrate intake, and history of acute respiratory infection were risk factors of underweight children aged 6-23 months in the Pagedangan sub-district